2018
DOI: 10.1016/j.chiabu.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal surveys in young, injured children: A systematic review

Abstract: Skeletal surveys (SSs) have been identified as a key component of the evaluation for suspected abuse in young children, but variability in SS utilization has been reported. Thus, we aimed to describe the utilization patterns, yield, and risks of obtaining SS in young children through a systematic literature review. We searched PubMed/MEDLINE and CINAHL databases for articles published between 1990 and 2016 on SS. We calculated study-specific percentages of SS utilization and detection of occult fractures and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 51 publications
(244 reference statements)
2
39
2
4
Order By: Relevance
“…The most common traumatic injuries identified on past admissions were orthopedic injuries, closed-head trauma, and burns. Additionally, having past traumatic injury was significantly associated with eventual hospitalizations for physical abuse, which indicates that a portion of the children with past abuse-related injuries [12,13,18,35] and subsequent hospitalization for abuse were likely cases of missed abuse. This failure of our healthcare system to detect abuse and attempt prevention of further abuse reveals an area for improvement in definitive identification and management of children with abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common traumatic injuries identified on past admissions were orthopedic injuries, closed-head trauma, and burns. Additionally, having past traumatic injury was significantly associated with eventual hospitalizations for physical abuse, which indicates that a portion of the children with past abuse-related injuries [12,13,18,35] and subsequent hospitalization for abuse were likely cases of missed abuse. This failure of our healthcare system to detect abuse and attempt prevention of further abuse reveals an area for improvement in definitive identification and management of children with abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of abuse is challenging, and physicians often miss the evidence of abuse that can lead to an appropriate intervention [1]. Successfully identifying abuse from particular injury patterns has been widely reported [11][12][13], yet despite this, abuse has been initially missed in 20%-30% of cases [12,14]. Consistent evidence has also shown that victims of child abuse have documented contact with the health care system, especially in the emergency department setting.…”
mentioning
confidence: 99%
“…1,8,11,30,31,33 Only specific diagnoses of abuse, or adverse social and parental circumstances preceding the date of first entry in the Out-of-home Care Register or within 15 days after that date, were categorized as exposure variables. Diagnoses of SDH, RH, rib fracture, or long bone fracture were selected that are claimed to have the highest positive predicative value for abuse, PPV of 0.69 for SDH, 9 0.97 for severe RH, 9 0.67 to 1.0 for rib fracture, 10,15,34 and 0.57 for long bone fracture. 11 Those diagnoses were combined in different categories and finally as one category, "SDH, RH, rib fracture, or long bone fracture" ( Table 1).…”
Section: Exposuresmentioning
confidence: 99%
“…The following diagnoses, subdural haemorrhage (SDH), retinal haemorrhage (RH), skull fracture, rib fracture, classic metaphyseal lesions (CMLs), long bone shaft fracture, apnoea, and seizures, are claimed to be specific for the diagnosis of abuse . However, the scientific solidity of the SBS/AHT diagnosis has been questioned .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation